2016
DOI: 10.1016/j.tranon.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Hypo-Vascular Liver Metastases Treated with Transarterial chemoembolization: Assessment of Early Response by Volumetric Contrast-Enhanced and Diffusion-Weighted Magnetic Resonance Imaging

Abstract: OBJECTIVE: To evaluate the value of anatomic and volumetric functional magnetic resonance imaging (MRI) in early assessment of response to trans-arterial chemoembolization (TACE) in hypovascular liver metastases. METHODS: This retrospective study included 52 metastatic lesions (42 targeted and 10 non-targeted) in 17 patients who underwent MRI before and early after TACE. Two reviewers reported response by anatomic criteria (Response Evaluation Criteria in Solid Tumor [RECIST], modified RECIST [mRECIST], and Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Recent studies (36)(37)(38) investigated the role of three-dimensional quantitative assessment of tumor response including whole-liver enhancing tumor burden as an imaging biomarker for prediction of survival in patients with hypo-and hypervascular liver malignancies after intra-arterial therapies and reported its usefulness. However, these studies were limited in terms of complete volumetric functional assessment because they did not incorporate changes in ADC that have been shown, in addition to the enhancement-based parameters, to change early after TACE and predict survival in both hypoand hypervascular liver malignancies (25,27,(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies (36)(37)(38) investigated the role of three-dimensional quantitative assessment of tumor response including whole-liver enhancing tumor burden as an imaging biomarker for prediction of survival in patients with hypo-and hypervascular liver malignancies after intra-arterial therapies and reported its usefulness. However, these studies were limited in terms of complete volumetric functional assessment because they did not incorporate changes in ADC that have been shown, in addition to the enhancement-based parameters, to change early after TACE and predict survival in both hypoand hypervascular liver malignancies (25,27,(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…Sobhani et al reported similar conclusions in a retrospective study of 17 patients who underwent transarterial chemoembolization (TACE), a similar embolizing therapy that uses chemotherapy drugs and microspheres as opposed to irradiated microspheres. They stated that a volumetric contrast-enhanced and diffusion-weighted MRI may prove effective in the early evaluation of treatment response in hypovascular lesions [ 24 ].…”
Section: Reviewmentioning
confidence: 99%
“…Another differentiation to HCC protocols should be the recommendations for bead sizes. According to the most recent evidence and since CRLM are less hypervascular compared to HCC, smaller bead sizes should be used as they have the potential to deliver the dose deeper into the tissue [ 35 , 36 , 37 , 38 ]. Studies found that smaller beads are not connected to more AEs [ 16 , 23 , 35 , 39 ].…”
Section: Discussionmentioning
confidence: 99%